PENGEMBANGAN POTENSI OBJEK WISATA KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA - ERITA S.Pd, M.Pd, YENI (Jurnal Pelangi : Research of Education and Development, 2011)
An effort of Conserving and developing the natural science can be done by introducing thetourist object to the citizen as well as to the people from other countries. Some tourist objectscan be found in Harau district of Lima Puluh Kota Regency such as : Kapalo Banda, SarasahTango, Lembah Harau, Kelok Sambilan, Gunung Sanggul and Sarasah Bunta. This researchwas a descriptive research which is used to analyze and report the way things are and with areal fact found in the frield. The purpose of this research was to find out and describe theNatural potential, the distribution and the power of attraction of the tourist object in Haraudistrict of Lima Puluh Kota Regency. The data was analyzed by analyzing the primary andsecondary data. The primary data was taken through the observation while the secondary datawas gained from tourism books and the reports of the department which dealing with thetourism. Both data were classified based on the classification that already been set up before.Finally, the data was analyzed by grouping them info the distribution of tourist object basedon the geographical condition and the Natural potential of tourist object in Harau district ofLima Puluh Kota Regency.